The non-radioactive local lymph node assay: Skin sensitisation and irritation testing - Brůčková, Lenka; Plodíková Petra, /; Čihák, Rostislav; Bílková, Zuzana (University of Pardubice, 2009)
This study was performed to investigate whether alternative endpoints of the local lymph node assay, non radioactive (LLNA-nR) like the ear weight and count cells would give additional information about the sensitizing/irritating potential of a tested substance. The legislation of REACH prefers alternative testing for skin sensitization and irritation. We have performed classic testing methods for skin irritation, for skin sensitization and alternative method LLNAnR with verified skin sensitizers, skin irritants and with some compounds, which were intended to be subjected to registration process according to REACH and other legislation rules. The aim of this paper was to test the hypothesis that it would be possible to use the LLNAnR testing method as single stand-alone method for the evaluation of sensitizing and irritation potential of untested chemicals. There is not only one test for simple determination of two skin toxicity endpoints, sensitization and skin irritation to date.